Jobs and justice : fighting discrimination in wartime Canada, 1939-1945 - Patrias, Carmela, 1950- (University of Toronto Press, 2012)
Juxtaposing a discussion of state policy with ideas of race and citizenship in Canadian civil society, Carmela K. Patrias shows how minority activists were able to bring national attention to racist employment discrimination during the Second World War and obtain official condemnation of such discrimination.